2009
DOI: 10.1002/jcop.20328
|View full text |Cite
|
Sign up to set email alerts
|

Network ties and mean lies: a relational approach to relational aggression

Abstract: The current study considers how the structure of peer networks facilitates or constrains children's opportunities to engage in relationally aggressive behaviors such as social exclusion and rumor spreading. Specifically, the influence of two network features, centrality and density, on relational aggression are explored using grade-level behavioral and social network data collected on a demographically diverse sample of 144 third through eighth grade urban elementary school students. As hypothesized, these net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 46 publications
4
34
2
Order By: Relevance
“…Indeed, while past studies have demonstrated that relationally aggressive children and adolescents generally possess a moderate to high number of social relationships [Faris and Felmlee, 2011;J.W. Neal, 2009], this study did not yield a positive main effect of number of relationships on children's relational aggression.…”
Section: Discussioncontrasting
confidence: 68%
“…Indeed, while past studies have demonstrated that relationally aggressive children and adolescents generally possess a moderate to high number of social relationships [Faris and Felmlee, 2011;J.W. Neal, 2009], this study did not yield a positive main effect of number of relationships on children's relational aggression.…”
Section: Discussioncontrasting
confidence: 68%
“…As was anticipated, a greater number of children in the home predicted an increase in the child’s relational aggression. In several studies, a positive association has been found between the number of peers in a child’s social network and their level of relational aggression (Faris & Felmlee, 2011; Neal, 2009). The results of this study are consistent with those findings, in that more children in the home led to higher levels of relational aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Another study looking at children in foster care found that the presence of more children in the home was associated with increased externalizing behavior problems (Harden & Whittaker, 2011). Although the relationship between household size and relational aggression has yet to be determined, studies focusing on peer contexts suggest that children with more peer relationships may exhibit heightened relational aggression because there are more opportunities for the child to use relational aggression (Faris & Felmlee, 2011; Neal, 2009). Resource dilution theory posits that available resources in the home, such as parents’ time and energy, decreases as the number of children in the home increases (Downey, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the techniques used for the investigation of the relationships that exist between stakeholders (Reed et al 2009). SNA consists of a set of analytical techniques to transform individual responses into maps of network structure, allowing researchers to quantify the structure of relationships between the individuals (Neal 2009). SNA is considered an important support tool in participatory planning processes (Prell et al 2009), particularly when decision makers are facing multiple use preferences and diverse objectives, as is the case of natural resources management (Bodin and Crona 2009;Hahn et al 2006).…”
Section: Analytical Categorisation Of Stakeholders Identified By the mentioning
confidence: 99%